2012
DOI: 10.1002/jbm.a.34127
|View full text |Cite
|
Sign up to set email alerts
|

Argon‐based atmospheric pressure plasma enhances early bone response to rough titanium surfaces

Abstract: This study investigated the effect of an Argon-based atmospheric pressure plasma (APP) surface treatment operated chairside at atmospheric pressure conditions applied immediately prior to dental implant placement in a canine model. Surfaces investigated comprised: rough titanium surface (Ti) and rough titanium surface + Argon-based APP (Ti-Plasma). Surface energy was characterized by the Owens-Wendt-Rabel-Kaelble method and chemistry by X-ray photoelectron spectroscopy (XPS). Six adult beagles dogs received tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 49 publications
8
78
3
6
Order By: Relevance
“…Plasma processes are often applied for cleaning and sterilization of dental implants after other surface treatments have been carried out, but they have also been tested for the acceleration of osseointegration [28][29][30][31] and the application of antibacterial properties to implants [28,29,32]. Argon and oxygen are the most used gases for these applications [28][29][30][31][32][33]. Plasma treatments also include plasma immersion ion implantation (PIII) processes, where plasma is used to produce ions, which are accelerated towards the surface of the treated sample and are implanted into it [33].…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…Plasma processes are often applied for cleaning and sterilization of dental implants after other surface treatments have been carried out, but they have also been tested for the acceleration of osseointegration [28][29][30][31] and the application of antibacterial properties to implants [28,29,32]. Argon and oxygen are the most used gases for these applications [28][29][30][31][32][33]. Plasma treatments also include plasma immersion ion implantation (PIII) processes, where plasma is used to produce ions, which are accelerated towards the surface of the treated sample and are implanted into it [33].…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…10 When the Ti surface experienced various types of APP treatments, the APP eliminated surface carbon contaminations (i.e., activation), increased surface wettability, facilitated adsorption of FN and, consequently, facilitated cell adhesion and proliferation, including those of osteoblastic cells. 5,8,[11][12][13][14] However, to our knowledge, detailed mechanistic investigations from a biological perspective have not been performed. To provide additional data and to better understand the effects of APP, we used a nitrogen gas-based APP system in this study to modify a chemically polished commercially pure Ti (CP-cpTi) surface and examined the responses of human prenatal-derived osteoblastic cells to the APP-treated CP-cpTi surface at the molecular level.…”
Section: Introductionmentioning
confidence: 95%
“…Correspondence to: T. Kawase (e-mail: kawase@dent.niigata-u.ac.jp) Contract grant sponsor: Grant-in-Aid for New Market Development by the Industrial Creation for 2012 from the Niigata Industrial Creation Organization and JSPS KAKENHI; contract grant number: 24390443 surface energy and to modify the oxide layer that interacts with the proteins and cells of the surrounding tissue. 8,9 Thus, plasma treatment is expected to improve the adhesion of the surrounding tissue. 4 However, the conventional plasma treatment method requires appropriate material sizes for the vacuum reactor and therefore limits the size and composition of the substrates to be modified.…”
Section: Introductionmentioning
confidence: 99%
“…Argon is chemically very inactive and has been used to provide an inert atmosphere during deposition. It has been shown that argon protection could effectively reduce the air contaminants on acid-etched Ti implant surfaces and maintain the surface hydrophilicity and biological activity of implants [30,31], enhancing the early bone formation on Ti surfaces [30,32]. Nitrogen is a chemically neutral gas and does not change the biological properties of the samples.…”
Section: Introductionmentioning
confidence: 99%